(3GdeHgL aj JaSjQ CSeGA TYQGA GdMeGSIs - (3YKeGf Hf Lfj GdehUdj, CHh GdaJM, GHf Lfj,J (B392 (3g` s
(3ChdgG (B:s
(3gPG JaSjQ CSeGA TYQGA GdMeGSI hjfHZi Cf jYde Cf ai Pdc YdekG cKjQkG hJOQHkG fGaYkG jLH Cf JbOe CeGe Pdc PcQ CMhGd gPg GdCSeGA s
(3BNQgG (B:s
(3bGd Gddg JYGdi (B: ( (3hCZWT djdgG hCNQ VMGgG (B) (3Je JaSjQ CSeGA TYQGA GdMeGSI hGdMeO ddg QH GdYGdejf hUdhGJg Ydi NjQJg ef Ndbgg eMeO hBdg GdWjHjf GdWGgQjf hSdGeg s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B204 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B251 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B652s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
(3eQchfGJ ef GdCOH (B- (3ecJHI YGQa MceJ HGdeOjfI GdefhQI (B((3COH (B732) s
Keywords: (3GdCOHs